2019
DOI: 10.1002/chem.201903916
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐Alkyl and N‐H‐Carbazoles through SNAr‐Based Aminations of Dibenzothiophene Dioxides

Abstract: Alkyl amines have become available for the synthesis of diverse N‐alkyl carbazoles through twofold SNAr aminations of dibenzothiophene dioxides by using alkali metal bases. Of particular importance is the choice of counter cations on alkali metal bases, that is, i) the use of Li base for the efficient intermolecular reaction and ii) the sequential addition of heavier alkali metal bases (Na, K, or Cs) to promote intramolecular cyclization in a one‐pot manner. This protocol also enables the cascade synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Recently, it has been reported that dibenzothiophenes can be converted into a variety of ring systems, such as dibenzosiloles, dibenzophospholes, fluorenes, and carbazoles [ 22 , 23 , 24 , 25 , 26 ]. Transformation to dibenzosiloles and dibenzophospholes involves (1) the generation of 1,1′-dianions via desulfurative dilithiation with lithium metal and (2) the subsequent reaction of the resulting 1,1′-dianions with silicon and phosphorus electrophiles, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that dibenzothiophenes can be converted into a variety of ring systems, such as dibenzosiloles, dibenzophospholes, fluorenes, and carbazoles [ 22 , 23 , 24 , 25 , 26 ]. Transformation to dibenzosiloles and dibenzophospholes involves (1) the generation of 1,1′-dianions via desulfurative dilithiation with lithium metal and (2) the subsequent reaction of the resulting 1,1′-dianions with silicon and phosphorus electrophiles, respectively.…”
Section: Introductionmentioning
confidence: 99%
“… 1 They can also serve as versatile building blocks for further modification or as reagents in many chemical transformations. 2 Accordingly, selective incorporation of sulfonyl moieties into organic commodities has received considerable attention in both chemistry and biology. 3 Conventional approaches include Friedel–Craft type sulfonylation of arenes, 4 oxidation of sulfides, 5 and nucleophilic aromatic substitution (S N Ar).…”
Section: Introductionmentioning
confidence: 99%
“…Dibenzothiophene dioxides 1b, [22] 1c, [22] 1d, [22] and imine 5 [28] were prepared according to the literature procedures.…”
Section: Preparation Of Substratesmentioning
confidence: 99%